Diseño de un módulo de cultivos hidropónico FVH para la crianza de animales de corral basado en IOT. - Llugsha Siza, Lenin Bladimir (2021)
The research project deals with the design of a hydroponic green fodder (FVH) cultivation module, which allows germination, cultivation and harvesting on trays without substrate, using fertigation as a fertilization method. The control and monitoring of the variables involved in the plant are alternatives that farmers must put into practice in their crops, in order to save water resources and evaluate the growth of forage from germinated seeds in a variety of cereals. In this work, the sprinkler irrigation system applied to hydroponic agriculture is presented, for which an HMI (human-machine interface) is developed, which allows continuous monitoring of humidity, temperature. In Unity 2019.0.2 f1 software, virtual simulation is shown. At the same time on the ThingSpeak web you can store, access and manage equipment operation data in real time of the behavior of the aforementioned variables, for the data link in the cloud the ESP8266 Module was used with the Arduino UNO board and a private IP address, in addition the controllers activate and deactivate (On - Off), to have a heated forage cultivation area, at the same time the control of a Timer for the irrigation system. Finally, the design of the module consists of a chapel-type greenhouse, developed under the requirements of a hydroponic system according to the (FAO), the optimal cultivation variables were also verified, which will help production both in time, quality, free of fertilizers. and lower cost.